Garnet type solid electrolyte with interface modification layer, preparation method and application of garnet type solid electrolyte in lithium metal symmetric battery

By constructing the Ga2O3 modification layer on the surface of the garnet-type solid electrolyte, the problem of high interface resistance and poor cycle stability when it comes into contact with the lithium metal interface is solved, lower interface resistance and higher critical current density are achieved, while enhancing the Air stability of electrolytes.

CN119495806AInactive Publication Date: 2025-02-21JILIN UNIVERSITY
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202510080049.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-19
Publication Date
2025-02-21
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The interface contact between garnet solid electrolyte and lithium metal has problems of high interface resistance and poor cycle stability, resulting in limited application in lithium metal symmetrical batteries.

Method used

Ga2O3 modified layer is constructed on the surface of the garnet solid electrolyte, and the Ga2O3 layer is deposited by radio frequency magnetron sputtering technology to control its thickness between 5~1000 nm, enhancing interface contact and wettability.

Benefits of technology

Through the Ga2O3 modification layer, the interface resistance is significantly reduced, from 992.2 Ω·cm-2 to 9.3 Ω·cm-2, and the critical current density of lithium symmetric batteries is increased from 0.1 mA·cm-2 to 0.5 mA· cm-2, while enhancing the air stability of the electrolyte.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119495806A_ABST
    Figure CN119495806A_ABST
Patent Text Reader

Abstract

The invention discloses a garnet type solid electrolyte with an interface modification layer, a preparation method and application of the garnet type solid electrolyte in a lithium metal symmetric battery, and belongs to the technical field of lithium metal symmetric batteries. The interface modification layer is a Ga2O3 modification layer which is constructed on the surface of the garnet type solid electrolyte and has the thickness of 5-1000 nm. The preparation method comprises the following steps: depositing the Ga2O3 modification layers on the surfaces of the two sides of the garnet type solid electrolyte by using a radio frequency magnetron sputtering technology; the crystallinity, the O vacancy and the thickness of the modification layer are accurately regulated and controlled by controlling the temperature, the O2 partial pressure and the deposition time. The interface modification layer provided by the invention can improve the interface contact between an electrolyte material and lithium metal, enhance the wettability of the electrolyte to lithium, reduce the interface resistance and improve the critical current density of the lithium symmetric battery; meanwhile, due to the existence of the compact modification layer, H2O and CO2 in the air are prevented from being in contact with the electrolyte, and the air stability of the electrolyte is enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium metal symmetrical batteries, and in particular relates to a garnet-type solid electrolyte with an interface modification layer, a preparation method and application thereof in lithium metal symmetrical batteries. Background Art

[0002] Energy plays a vital role in all aspects of human life. Lithium-ion batteries that can achieve efficient energy storage and conversion are widely used in society. However, due to the huge safety risks of traditional lithium-ion batteries using organic liquid electrolytes, people are gradually turning to safe and reliable solid electrolytes. 7 La 3 Zr 2 O 12 (LLZO) has high room temperature ionic conductivity (>10 -4 S cm -1 ), high mechanical strength, good thermal stability and relative stability to lithium metal anode, and has attracted extensive attention and research.

[0003] However, garnet-type solid electrolytes are prone to H + / Li + exchange reaction, and then with CO 2 The reaction generates Li 2 CO 3 , resulting in extremely high interfacial resistance and extremely poor cycle stability. At the same time, when garnet-type solid electrolytes doped with elements such as Fe, Nb, and Ti come into contact with lithium metal, they will react to produce an interfacial insulating layer. In 2016, Miaofang Chi (Nano Letters, 2016(11): 7031-7036) et al. found that when cubic LLZO comes into contact with lithium metal, as Li + The injection of 20% LLZO into the garnet electrolyte will form a thin layer of tetragonal LLZO with low ionic conductivity, resulting in high interface resistance. Therefore, solving the interface problem of solid-solid contact between garnet-type solid electrolyte and lithium metal becomes the key to achieving the widespread application of all-solid-state batteries.

[0004] Introducing a modified layer between Li and LLZO is a very effective solution. Yong Yang (Advanced Functional Materials, 2023, 33. 2209120) et al. used LiPO 2 F 2 With the passivation layer Li 2 CO 3 The reaction generates a modified layer, reducing the interface resistance to 5.1 Ω·cm -2Li-Jun Wan (Advanced Functional Materials, 2022, 32(24). 2201498) et al. introduced Ta by spin coating and calcination. 2 O 5 Modification layer, reducing the interface resistance to 9Ω·cm -2 However, these methods have difficulty in forming dense and uniform modified layer films, and do not explicitly mention the reaction with lithium metal, which results in a lack of good lithium ion migration channels at the interface.

[0005] Therefore, it is necessary to further explore new modified layers and their preparation methods. 2 O 3 When heated, it undergoes an alloying reaction with lithium metal to form a dense and uniform modified interface for lithium ion migration, which is beneficial for solving the interface contact problem between garnet-type solid electrolyte and lithium metal. Summary of the invention

[0006] In view of the above problems, the object of the present invention is to provide a garnet-type solid electrolyte with an interface modification layer, a preparation method and its application in a lithium metal symmetric battery, aiming to solve the problems of poor air stability, poor wettability to lithium metal and high interface resistance of garnet-type solid electrolyte.

[0007] The interface modification layer of the present invention is Ga constructed on the surface of the garnet-type solid electrolyte. 2 O 3 The modification layer has a thickness of 5 to 1000 nm. The preparation method of the interface modification layer comprises: depositing a layer of Ga on the surface of the garnet solid electrolyte by using radio frequency magnetron sputtering technology. 2 O 3 The modification layer is formed by controlling the temperature, O 2 The crystallinity, O vacancies and nanolayer thickness can be precisely controlled by partial pressure and deposition time. The interface modification layer of the garnet-type solid electrolyte provided by the present invention can improve the interface contact between the electrolyte material and lithium metal, enhance the wettability of the electrolyte to lithium, reduce the interface resistance, and increase the critical current density of the lithium symmetric battery; at the same time, due to the presence of the dense modification layer, H in the air is prevented from 2 O and CO 2 The contact with the electrolyte enhances the air stability of the electrolyte.

[0008] One of the purposes of the present invention is to provide a method for preparing a garnet-type solid electrolyte having an interface modification layer, the steps of which are as follows: (1) A garnet-type solid electrolyte ceramic sheet was prepared by a high-temperature solid phase method. The chemical formula of the garnet-type solid electrolyte is Li 7-x La 3 Zr2-x Ta x O 12 , where 0<x≤1; the crystal structure is a cubic phase structure, and the Li content is regulated by adjusting the x value; (2) grinding and polishing both sides of the garnet-type solid electrolyte ceramic sheet prepared in step (1) to obtain a garnet-type solid electrolyte substrate; (3) Using radio frequency magnetron sputtering, Ga 2 O 3 Modification layer is formed to obtain a garnet-type solid electrolyte having interface modification layers on both sides of the surface.

[0009] Furthermore, the polishing method in step (2) is hand polishing with SiC sandpaper to achieve smooth and flat surfaces on both sides, and the thickness of the garnet solid electrolyte substrate after polishing is 0.5-2 mm; Furthermore, the background vacuum of the radio frequency magnetron sputtering method in step (3) is less than 10 -4 Pa, working pressure is 0.1~10 Pa, power is 60~120 W; Furthermore, the RF magnetron sputtering method in step (3) uses Ar-O 2 Mixed gas, of which O 2 The partial pressure is 0~80%; Furthermore, the deposition time of the radio frequency magnetron sputtering method in step (3) is 10 to 240 min, the garnet solid electrolyte substrate is placed on the substrate, the substrate temperature is 25 to 600°C, and the Ga 2 O 3 The thickness of the modified layer is 5~1000 nm.

[0010] The second object of the present invention is to provide a garnet-type solid electrolyte with an interface modification layer, which is prepared by the above method.

[0011] The third object of the present invention is to provide the use of the above-mentioned garnet-type solid electrolyte with an interface modification layer in the preparation of a lithium metal symmetric battery, and the specific steps are as follows: (1) A 0.05-0.3 mm thick lithium source is attached and pressed onto both sides of a garnet-type solid electrolyte substrate with an interface modification layer to form a sandwich structure of Li / solid electrolyte / Li; (2) heating the sandwich structure obtained in step (1) at a certain temperature for a period of time, and then naturally cooling it to room temperature; (3) A 0.2-0.5 mm thick current collector is used as the conductive buffer layer of the negative electrode, and the button-type battery is pressurized and packaged in the order of “positive electrode shell / sandwich structure / stainless steel gasket / current collector / negative electrode shell”, thereby realizing the application of garnet-type solid electrolyte with an interface modification layer in the preparation of lithium metal symmetric batteries.

[0012] Further, the lithium source in step (1) is lithium metal; Furthermore, the heating temperature in step (2) is 230-350°C, and the heating time is 1 s-30 min; Furthermore, the current collector in step (3) is one or more of nickel foam, carbon fiber, and foil (stainless steel, aluminum, copper, nickel, platinum, etc.); the button cell specification is one of 2032 and 2025, and the packaging pressure is 1-10 MPa.

[0013] Compared with the prior art, the present invention has the following outstanding features and beneficial effects: 1. Propose to introduce Ga at the interface between metallic lithium and garnet solid electrolyte 2 O 3 Modification layer; 2. Ga deposited by RF magnetron sputtering 2 O 3 The modified layer is dense and uniform, isolating the solid electrolyte from the air, hindering the formation of the passivation layer, and improving the air stability of the solid electrolyte; 3. Ga 2 O 3 The modified layer has higher wettability to lithium metal and reacts with lithium metal during heating, thereby enhancing the interface contact and reducing the interface resistance. It is also beneficial to the interface treatment during the battery charging and discharging process. + Uniform migration inhibits the formation of lithium dendrites. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 X-ray diffraction patterns of the solid electrolytes prepared in Examples 1 and 2 of the present invention; Figure 2 Comparative Example 1 of the present invention does not deposit Ga 2 O 3 X-ray diffraction pattern of the modified solid electrolyte after exposure to air for 30 days; Figure 3 The AC impedance spectra of the lithium symmetrical batteries assembled in Example 2 of the present invention and Comparative Example 1 at 25°C; Figure 4 A comparative bar graph of interface resistances calculated from AC impedance spectra of lithium symmetric batteries assembled in Example 2 of the present invention and Comparative Example 1; Figure 5This is a critical current density test diagram of the lithium symmetrical battery assembled in Example 2 of the present invention; Figure 6 This is a critical current density test diagram of the lithium symmetrical battery assembled in Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0015] The present invention is further described in detail below in conjunction with specific embodiments. It should be emphasized that the following description is merely exemplary and is not intended to limit the scope of the present invention and its application. In addition, in the following description, the description of known structures and technologies is omitted to avoid unnecessary confusion of the concept of the present invention.

[0016] The EIS test in the following specific implementation manner is to test the prepared lithium metal symmetrical battery using an impedance analyzer, the test frequency range is 1 MHz~10 Hz, the voltage amplitude is 100 mV, and the interface resistance value is obtained by dividing the fitting result by the total interface area.

[0017] The critical current density test in the following specific implementation is performed using a LAND CT2001A charge and discharge instrument. The test environment is 25°C and the starting point is 0.1 mA·cm -2 , with a step size of 0.1 mA·cm -2 , each step lasts 20 min.

[0018] Example 1: Li 6.4 La 3 Zr 1.4 Ta 0.6 O 12 The preparation of solid electrolyte, the specific steps are as follows: (1) Place lanthanum oxide in a muffle furnace and heat it at 900°C for 12 h; (2) 2.759 g of lithium hydroxide monohydrate, 7.331 g of lanthanum oxide, 2.588 g of zirconium oxide and 1.988 g of tantalum oxide were mixed and placed in an agate ball mill with a ball-to-material mass ratio of 3:1. 40 mL of isopropanol was added and the planetary ball mill speed was 350 rpm. The ball milling time was 12 h. After the ball milling, the separated suspension was dried in an oven at 80 °C and then pre-calcined in a muffle furnace at 900 °C (heating rate of 5 °C / min) for 5 h to obtain 13.3 g of Li 6.4 La 3 Zr 1.4 Ta 0.6 O 12 Solid electrolyte precursor powder; (3) The solid electrolyte precursor powder obtained in step (2) was placed in an agate ball mill with a ball-to-material mass ratio of 3:1, 40 mL of isopropanol was added, the planetary ball mill speed was 350 rpm, and the ball milling time was 12 h. After the ball milling, the separated suspension was dried in an oven at 80 °C to obtain 13.1 g of powder sample; (4) 1.5 g of the powder sample obtained in step (3) was kept at a pressure of 400 MPa for 10 min to obtain a solid electrolyte sample blank, the blank was buried with the same powder, and then sintered in a muffle furnace at 1230°C for 5 h to obtain a solid electrolyte ceramic sheet, with a heating rate of 5°C / min; (5) The two sides of the solid electrolyte ceramic sheet were polished with 400 mesh, 2000 mesh, and 5000 mesh SiC sandpaper in sequence to obtain a garnet-type solid electrolyte substrate (LLZTO) with a thickness of 1.5 mm.

[0019] The XRD test of the garnet solid electrolyte substrate (LLZTO) obtained above is as follows: Figure 1 As shown, compared with the standard card (PDF#80-0457), the obtained LLZTO phase is a pure cubic phase.

[0020] Example 2: The preparation steps of the garnet-type solid electrolyte substrate (LLZTO) are the same as those of Example 1; Ga was prepared on both sides of the substrate by radio frequency magnetron sputtering. 2 O 3 Modification layer, the specific steps are as follows: (1) Fix the polished substrate on the base and reduce the pressure in the magnetron sputtering chamber to less than 10 -4 Pa, working power is 120 W; (2) Pass in Ar-O 2 Mixed gas, working pressure is 1 Pa, O 2 The partial pressure is 30% and the base temperature is 25°C; (3) The deposition time is 30 min, and Ga 2 O 3 Garnet-type solid electrolyte with modified layer, Ga 2 O 3 The thickness of the modified layer is 75 nm.

[0021] For the above deposited Ga 2 O 3 The solid electrolyte of the modified layer is just deposited (Ga 2 O 3 -LLZTO) and 30 days exposure in air (Ga 2 O 3-LLZTO-30 days) and then XRD tests were performed. The results are as follows Figure 1 As shown, low temperature deposited Ga 2 O 3 The modified layer has an amorphous structure with no obvious diffraction peaks, and no Li was detected after exposure to air for 30 days. 2 CO 3 The mixed peaks prove that Ga 2 O 3 The presence of the modified layer enhances the air stability of the garnet-type solid electrolyte.

[0022] Using deposited Ga 2 O 3 The solid electrolyte of the modified layer is used to assemble a lithium symmetric battery. The specific steps are as follows: (1) Cut the 0.05 mm thick lithium metal sheet into pieces with an area of ​​0.5 cm 2 The disc is attached and pressed on both sides of the garnet-type solid electrolyte with an interface modification layer to form a Li / solid electrolyte / Li sandwich structure, and is placed on a stainless steel sheet; (2) Heat to 300°C, hold for 10 min, and then cool naturally; (3) Select 0.3 mm thick nickel foam as the current collector and pressurize it to 5 MPa to package a button cell with a specification of 2032.

[0023] The battery was tested by EIS at 25°C. Figure 3 As shown in the inset; the calculated interface resistance is 9.3Ω·cm -2 ,like Figure 4 As shown; the critical current density of the battery was tested at 25°C, with a starting point of 0.1 mA·cm -2 , step size is 0.1 mA·cm -2 , each step lasts 20 minutes, the test results are as follows Figure 5 As shown, the critical current density is 0.5 mA·cm -2 .

[0024] Example 3: The preparation steps of the solid electrolyte ceramic sheet are the same as those of Example 1; Ga 2 O 3 The preparation steps of the modified layer are the same as those of Example 2, except that the substrate temperature in step (2) is 150°C, and the deposition time in step (3) is 60 min. 2 O 3 The thickness of the modified layer is 170 nm; The steps for assembling the lithium symmetrical battery are the same as those in Example 2.

[0025] Example 4: The preparation steps of the solid electrolyte ceramic sheet are the same as those of Example 1; Ga 2 O 3 The steps for preparing the modified layer are the same as those in Example 2, except that the substrate temperature in step (2) is 200°C; The steps for assembling the lithium symmetrical battery are the same as those in Example 2.

[0026] Comparative Example 1: The preparation steps of the garnet-type solid electrolyte substrate are the same as those of Example 1; No preparation of Ga 2 O 3 Modification layer; For the above-mentioned Ga 2 O 3 The solid electrolyte with modified layer was exposed to air for 30 days and then XRD test was performed. Figure 2 As shown, significant Li 2 CO 3 Miscellaneous peaks; The steps for assembling the lithium symmetric battery are the same as those in Example 2. It should be noted that a non-interface-modified solid electrolyte ceramic sheet exposed to air for 0 days is used here.

[0027] The battery was tested by EIS at 25°C. Figure 3 As shown; the calculated interface resistance is 992.2 Ω·cm -2 ,like Figure 4 As shown; the critical current density of the battery was tested at 25°C, with a starting point of 0.1 mA·cm -2 , with a step size of 0.1 mA·cm -2 , each step lasts 20 minutes, the test results are as follows Figure 6 As shown, the critical current density is 0.1 mA·cm -2 .

[0028] In summary, the present invention provides a garnet-type solid electrolyte with an interface modification layer, a preparation method and its application in a lithium metal symmetric battery. From the test results obtained in the embodiment and the comparative example, it is not difficult to see that the Ga deposited by radio frequency magnetron sputtering 2 O 3 The modified layer hinders the formation of the passivation layer, and no Li was detected after exposure to air for 30 days. 2 CO 3 It appears, proving that it improves the air stability of solid electrolytes. 2 O 3 The modified layer has higher wettability to lithium metal, which enhances the interfacial contact and reduces the interfacial resistance from 992.2 Ω·cm -2 Reduced to 9.3 Ω·cm -2, the critical current density is from 0.1 mA·cm -2 Increased to 0.5 mA·cm -2 .

[0029] It should be understood that the above specific embodiments of the present invention are only used to illustrate or explain the principles of the present invention, are preferred embodiments of the present invention, and do not constitute limitations on the present invention. Therefore, any modifications, equivalent substitutions, improvements, etc. made without departing from the spirit and scope of the present invention should be included in the protection scope of the present invention. In addition, the claims attached to the present invention are intended to cover all changes and modifications that fall within the scope and boundaries of the attached claims, or the equivalent forms of such scope and boundaries.

Claims

1. A method for preparing a garnet-type solid electrolyte having an interface modification layer, characterized in that: The steps are as follows: (1) A garnet-type solid electrolyte ceramic sheet was prepared by a high-temperature solid phase method. The chemical formula of the garnet-type solid electrolyte is Li 7-x LqCy 2-x Ta x O 12 , where 0<x≤1; the crystal structure is a cubic phase structure, and the Li content is regulated by adjusting the x value; (2) grinding and polishing both sides of the garnet-type solid electrolyte ceramic sheet prepared in step (1) to obtain a garnet-type solid electrolyte substrate; (3) Using a radio frequency magnetron sputtering method, a Ga2O3 modification layer is deposited on both side surfaces of the garnet-type solid electrolyte substrate obtained in step (2) to obtain a garnet-type solid electrolyte having an interface modification layer on both side surfaces.

2. The method for preparing a garnet-type solid electrolyte having an interface modification layer according to claim 1, characterized in that: The polishing method described in step (2) is hand polishing using SiC sandpaper to achieve a smooth and flat surface on both sides. After polishing, the thickness of the garnet-type solid electrolyte substrate is 0.5-2 mm.

3. The method for preparing a garnet-type solid electrolyte having an interface modification layer according to claim 1, characterized in that: The background vacuum of the radio frequency magnetron sputtering method described in step (3) is less than 10 -4 Pa, the working air pressure is 0.1~10 Pa, and the power is 60~120 W.

4. The method for preparing a garnet-type solid electrolyte having an interface modification layer according to claim 1, characterized in that: The RF magnetron sputtering method in step (3) uses an Ar-O2 mixed gas, wherein the O2 partial pressure is 0-80%.

5. The method for preparing a garnet-type solid electrolyte having an interface modification layer according to claim 1, characterized in that: The deposition time of the radio frequency magnetron sputtering method in step (3) is 10-240 min, the garnet solid electrolyte substrate is placed on the base, the temperature of the base is 25-600°C, and the thickness of the Ga2O3 modified layer is 5-1000 nm.

6. A garnet-type solid electrolyte having an interface modification layer, characterized in that: The method is prepared by any one of claims 1 to 5.

7. Use of the garnet-type solid electrolyte with an interface modification layer as claimed in claim 6 in the preparation of a lithium metal symmetric battery.

8. Use of a garnet-type solid electrolyte with an interface modification layer as claimed in claim 7 in the preparation of a lithium metal symmetric battery, characterized in that: The steps of this application are as follows, (1) A 0.05-0.3 mm thick lithium source is attached and pressed onto both sides of a garnet-type solid electrolyte substrate with an interface modification layer to form a sandwich structure of Li / solid electrolyte / Li; (2) heating the sandwich structure obtained in step (1) at a certain temperature for a period of time, and then naturally cooling it to room temperature; (3) A 0.2-0.5 mm thick current collector is used as the conductive buffer layer of the negative electrode, and the battery is pressurized and packaged into a button-type battery in the order of "positive electrode shell / sandwich structure / stainless steel gasket / current collector / negative electrode shell", thereby realizing the application of garnet-type solid electrolyte with an interface modification layer in the preparation of lithium metal symmetric batteries.

9. Use of a garnet-type solid electrolyte with an interface modification layer as claimed in claim 8 in the preparation of a lithium metal symmetric battery, characterized in that: The lithium source in step (1) is lithium metal; the heating temperature in step (2) is 230-350°C, and the heating time is 1 s-30 min; the current collector in step (3) is one or more of nickel foam, carbon fiber, and foil; the button cell specification is one of 2032 and 2025, and the packaging pressure is 1-10 MPa.

10. Use of a garnet-type solid electrolyte with an interface modification layer as claimed in claim 9 in preparing a lithium metal symmetric battery, characterized in that: The foil is made of stainless steel, aluminum, copper, nickel or platinum.

Citation Information

Patent Citations

  • Dark purple external amorphous transparent conductive film and preparation method thereof

    CN101661810A

  • Interfacial modification membrane for solid electrolyte for lithium battery and preparation method thereof

    CN102646801A

  • LLZO preparation method, thermal cell quasi-solid electrolyte, and preparation method thereof

    CN109879316A

  • Solar blind ultraviolet detector based on amorphous gallium oxide film and preparation method thereof

    CN110444618A

  • Preparation method of high-conductivity solid-state battery electrolyte for energy storage charging system battery

    CN113161607A